IMF Committee on Balance of Payments Statistics : Annual Report 2018. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2019)
The 2018 Annual Report of the IMF Committee on Balance of Payments Statistics provides an overview of trends in global balance of payments statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet